Optimalisasi sistem tata udara gedung perkantoran bertingkat dengan metode six sigma (Studi kasus gedung PT.Bank Aceh cabang Lhokseumawe) - Syamsuar Syamsuar (Politeknik Negeri Lhokseumawe, 2018)
The use of energy in the air system of PT. Bank Aceh Lhokseumawe branch annually averages 60 - 75% of total energy consumption in buildings. The purpose of this research is to optimize energy use in air system continuously using Six Sigma approach. The six sigma approach is expected to reduce the cost of using the air system system without neglecting the comfort level according to the national comfort standard (SNI). The problem faced by the air system is the existence of over cooling load (over cooling load), the value reaches the figure beyond the initial 60,000 watts planning capacity. The calculation results obtained actual average cooling load reached 75,580.3 watts. It is known that the cooling overload is caused by several factors, namely: the quantity of occupant / human, the air ventilation factor, the management factor of electric appliances usage, the lighting factor, and the solar radiation / transmission factor. Solutions to improve the air conditioning system by minimizing the factors that cause over cooling load. The results of the improvement get a cooling load of 57,340.9 watts which means savings of 24.2%, or monthly electrical energy savings of 4,428.324 kwh / month or equivalent to 50,739.888 kwh / year. Keywords: cooling load, six sigma, optimization, critical to quality